The journalistic shaping of heroes and anti-heroes on Twitter: Zelensky and Putin in the Ukraine war - Rivas-de-Roca, Rubén (2023)
Periods of international crisis, such as the war in Ukraine that began in February 2022, are very symbolic times. Due to the remoteness of this type of conflicts, the media still play an important role in the shaping of news items that reach citizens. However, this field also suffers the deep transformations that digital platforms have brought for journalism. In this context, this study aims to explore the mechanisms that the press uses to generate international leaders on Twitter. Specifically, we analyze how the media contribute to creating figures of hero, anti-hero or villain with Zelensky and Putin, similar to ancient antagonistic struggles. To this purpose, a discursive content analysis is applied to a sample of all tweets (n=1244) posted by the five main Spanish newspapers (El País, El Mundo, ABC, El Confidencial, elDiario.es) that referenced these two leaders, during the weeks before and after the start of the war. As a result, there is a greater number of mentions of Putin, together with a negative approach. The building of a dichotomous relationship also occurs through a Zelensky who usually acts as the subject, but with less active verbs than Putin. Nevertheless, differences are detected depending on the ideology and the technological nature of the newspaper. These findings, added to the fact that the public prefer to interact with messages that allude to Zelensky or both leaders, foster a debate about the implications of this underlying intentionality of the media.